(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Bleeding in vitreoretinal patients during and early after vitrectomy is still a challenge that needs to be addressed. Purpose: To assess the effect of irrigation fluid temperature on intraocular bleeding time in rabbits during vitrectomy. Material and Methods: Twelve Chinchilla rabbits (24 eyes) were included in this study and divided into four groups of 3 animals (6 eyes) each based on vitrectomy irrigation fluid temperature: group 1 (5° C), group 2 (10° C), group 3 (22° C), and group 4 (36° C). The ambient operating room temperature was between 22 °С and 24 °С. Results: The duration of intraocular bleeding in groups 1, 2, 3 and 4 was 88.3 ± 46.0 s, 34.8 ± 30 s, 63 ± 23.5 s, and 21.1 ± 9.5 s, respectively. Conclusion: In a rabbit model of intraocular bleeding, use of irrigation fluid of 36 °С (i.e., conditions of mild hypothermia) resulted in shorter intraocular bleeding in the perioperative period of vitrectomy compared to conventional use of room-temperature irrigation fluid (21.1 ± 9.5 s against 63 ± 23.5 s). Mild hypothermia may be recommended for use in vitreoretinal surgery in patients with a high risk of bleeding.